Awesome orcas (Virginia, United states of America The national wildlife federation, 2017)
In this book, readers will be introduced to the exciting world of orcas. Learn how these majestic mammals see, communicate, and hunt, and how they use camouflage to survive in the wild
Science (marine creature)
Keywords: Aquatic ecology